2020
DOI: 10.3389/fpls.2020.00035
|View full text |Cite
|
Sign up to set email alerts
|

The Alcohol and Epoxy Alcohol of Zingiberene, Produced in Trichomes of Wild Tomato, Are More Repellent to Spider Mites Than Zingiberene

Abstract: Allelochemicals that are present in trichome secretions of wild tomato species play a major role in mediating interactions with arthropods, often conferring a high level of resistance via antibiosis and antixenosis. Many accessions of the wild tomato relative, Solanum habrochaites (S.h), possess high levels of resistance to arthropods. The monocyclic sesquiterpene hydrocarbon, 7-epi-zingiberene, is a major defensive component found in trichome secretions of certain accessions of S.h. We have used LA2329, an S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The (semi-)volatile mono-and sesquiterpenes that are, at least predominantly, produced and stored in type-VI trichomes serve as another important class of metabolites implicated in the defence against pests [ 24 , 38 40 ]. The sesquiterpenes 7-epizingiberene and R-curcumene produced by wild tomato S. habrochaites PI127826 repel whiteflies and 7-epizingiberene alcohol derivatives have a repellent effect on the spider mite Tetranychus urticae [ 41 , 42 ]. Also, 2,3-dihydrofarnesoic acid from S. habrochaites accessions LA1363 and LA1927 act on spider mites as a repellent [ 43 ] and type-VI trichomes of S. habrochaites accession LA1777 produce a mixture of bergamotoic-and santanaloic acids that confers resistance against the tomato fruitworm ( Helicoverpa zea ) and the beet armyworm ( Spodoptera exigua) [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…The (semi-)volatile mono-and sesquiterpenes that are, at least predominantly, produced and stored in type-VI trichomes serve as another important class of metabolites implicated in the defence against pests [ 24 , 38 40 ]. The sesquiterpenes 7-epizingiberene and R-curcumene produced by wild tomato S. habrochaites PI127826 repel whiteflies and 7-epizingiberene alcohol derivatives have a repellent effect on the spider mite Tetranychus urticae [ 41 , 42 ]. Also, 2,3-dihydrofarnesoic acid from S. habrochaites accessions LA1363 and LA1927 act on spider mites as a repellent [ 43 ] and type-VI trichomes of S. habrochaites accession LA1777 produce a mixture of bergamotoic-and santanaloic acids that confers resistance against the tomato fruitworm ( Helicoverpa zea ) and the beet armyworm ( Spodoptera exigua) [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bioactivity assays performed here point to a specific toxicity of 9H10epoZ, for which a clear, concentration-dependent effect was observed against B. tabaci ( Figure 6). A recent study also identified 9HZ and 9H10epoZ as potent repellents of spider mites, Tetranychus urticae (Dawood and Snyder, 2020), further confirming these compounds to be of potential relevance for resistance against arthropod Figure 6. Whitefly toxicity assays of (4R,7R)-zingiberene and its oxidized derivatives.…”
Section: From a Volatile Signalling Molecule To A Toxic Derivativementioning
confidence: 72%
“…For example, bioassays have shown that naïve honeybees are attracted to apple floral scent [ 50 ]. However, many plants, including tomato, release repellent volatile organic compounds to defend against insect herbivores [ 51 , 52 , 53 ]. Plant defense against herbivores may show a trade-off with pollinator attraction [ 54 ].…”
Section: Discussionmentioning
confidence: 99%